Tantangan Pembelajaran di Era Digital dalam Membentuk Karakter Religius Siswa di Sekolah Menengah Atas Muhamadiyah 2 Surabaya - Mollah, Moch. Kalam (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
The advancement of digital technology has had a significant impact on various aspects of life, including education. This study aims to explore the role of Islamic Education (PAI) teachers in shaping students' religious character in the digital era, focusing on the challenges and teaching strategies involved. A qualitative approach was employed, utilizing observation and in-depth interviews with teachers and students at SMA Muhammadiyah 2 Surabaya. The findings reveal that PAI teachers play strategic roles as spiritual guides, digital information filters, behavioral role models, and facilitators of digital literacy. Collaboration with parents and the community also serves as a critical element in strengthening students' religious character formation. This study emphasizes the importance of a holistic approach that integrates religious education, digital technology, and character values in teaching practices. The findings are expected to contribute to the development of character-based curricula and innovative teaching strategies